2020
DOI: 10.3168/jds.2020-18686
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating acute inflammation's effects on hepatic triglyceride content in experimentally induced hyperlipidemic dairy cows in late lactation

Abstract: Inflammation appears to be a predisposing factor and key component of hepatic steatosis in a variety of species. Objectives were to evaluate effects of inflammation [induced via intravenous lipopolysaccharide (LPS) infusion] on metabolism and liver lipid content in experimentally induced hyperlipidemic lactating cows. Cows (765 ± 32 kg of body weight; 273 ± 35 d in milk) were enrolled in 2 experimental periods (P); during P1 (5 d), baseline data were obtained. At the start of P2 (2 d), cows were assigned to 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 76 publications
0
3
0
4
Order By: Relevance
“…In addition, BMECs, as one of the main cells of mammary tissue, are not only important immune cells, but also a major cell population for lactation in cows ( 28 , 35 ). When mastitis occurs in cows, mastitis is well known to seriously affect milk production and quality ( 11 , 19 , 34 ). Yusaku Tsugami et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, BMECs, as one of the main cells of mammary tissue, are not only important immune cells, but also a major cell population for lactation in cows ( 28 , 35 ). When mastitis occurs in cows, mastitis is well known to seriously affect milk production and quality ( 11 , 19 , 34 ). Yusaku Tsugami et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the inflammatory response is a self-protective mechanism of the body, that has the function of removing pathogenic bacteria, eliminating bacterial toxins and repairing damaged tissues ( 10 ). When the autoimmunity of the body is able to clear and kill pathogenic bacteria and repair the damage, mastitis will recover on its own; otherwise, the inflammatory response will become more intense, not only damaging the mammary tissue and reducing milk production; but also even endangering the life of cow ( 11 ). Several studies have shown that the inflammatory response is closely linked to autophagy, that autophagy plays a key role in maintaining inflammatory homeostasis, and that enhancing autophagy can reduce damage to the inflammatory response ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Es ergab sich zu Beginn der Infu sion ein transienter Anstieg von NEFA, aber keine Erhöhung des Leberfettgehalts. Diese Arbeitsgruppe hat diese Untersuchungen fortgesetzt [103] und Kühen intravenös Fett oder Fett plus LPS für 16 h infundiert. Die Infusion verursacht in beiden Gruppen einen Anstieg der NEFA im Blut und eine heftige Entzündungsreaktion in der Gruppe Fett plus LPS.…”
Section: Entzündung Oxidativer Und Endoplasmatischer Stressunclassified
“…Dieser akute Versuch bestätigt zwar die Auslösung einer Entzündungsreaktion durch LPS, aber nicht die Arbeitshypothese einer Beteiligung von LPS an der Pathogenese der Leberverfettung. Die Autoren schließen aber eine eventuell chronische Wirkung von LPS an diesem Krankheitsgeschehen nicht aus [103].…”
Section: Entzündung Oxidativer Und Endoplasmatischer Stressunclassified
See 1 more Smart Citation